Shanghai and the Edges of Empires - Meng, Yue, 1956- (Book collections on Project MUSE., 2006)
Even before the romanticized golden era of Shanghai in the 1930s, the famed Asian city was remarkable for its uniqueness and East-meets-West cosmopolitanism. Meng Yue analyzes a century-long shift of urbanity from China's heartland to its shore. During the period between the decline of Jiangnan cities such as Suzhou and Yangzhou and Shanghai's early twentieth-century rise, the overlapping cultural edges of a failing Chinese royal order and the encroachment of Western imperialists converged. Simultaneously appropriating and resisting imposing forces, Shanghai opened itself to unruly, subversive.